2016
DOI: 10.1097/qai.0000000000000979
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and Operational Research

Abstract: Background Rates of screening for bacterial sexually transmitted infections (STI) among men who have sex with men in HIV care settings remain low despite high prevalence of these infections. STI self-testing may help increase screening rates in clinical settings. Methods We implemented an STI self-testing program at a large, urban HIV care clinic, and evaluated its effectiveness and acceptability. We compared measures obtained during the first year of the STI Self-testing Program (Intervention Year, April 1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 15 publications
2
30
0
Order By: Relevance
“…Compared to pre-intervention, there was a 91.8% relative increase in complete testing (i.e. all three anatomical sites) after implementation of the self-testing program (16% vs. 31%, p<0.001) [50]. Although there were statistically significant increases in urethral, pharyngeal, and rectal screening when analyzed separately, screening for gonorrhea and chlamydia was still low with less than 50% of clinic patients tested for each anatomical site.…”
Section: Interventions To Improve Hiv Care-based Sti Screeningmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to pre-intervention, there was a 91.8% relative increase in complete testing (i.e. all three anatomical sites) after implementation of the self-testing program (16% vs. 31%, p<0.001) [50]. Although there were statistically significant increases in urethral, pharyngeal, and rectal screening when analyzed separately, screening for gonorrhea and chlamydia was still low with less than 50% of clinic patients tested for each anatomical site.…”
Section: Interventions To Improve Hiv Care-based Sti Screeningmentioning
confidence: 99%
“…Although there were statistically significant increases in urethral, pharyngeal, and rectal screening when analyzed separately, screening for gonorrhea and chlamydia was still low with less than 50% of clinic patients tested for each anatomical site. Syphilis screening was above 50%, but there was no significant difference before and after intervention (63.3% vs. 64.6%, p=0.44) [50].…”
Section: Interventions To Improve Hiv Care-based Sti Screeningmentioning
confidence: 99%
“…8,9 Clinicians perceived that the self-testing program increased the likelihood of STI testing, and our quantitative effectiveness analysis found that STI testing of pharyngeal, rectal, and urethral NG/CT significantly increased post-intervention. 17 The timesaving benefit seemed to facilitate clinician referral to the self-testing process during a clinic visit and contributed to the increase in testing coverage. In a study by Richardson et al, most surveyed physicians reported that they would use vaginal swab self-testing in women for CT testing, but some providers who did not prefer self-testing were concerned about patients conducting self-testing incorrectly and the time required to instruct patients on self-testing.…”
Section: Discussionmentioning
confidence: 99%
“…The STI self-testing program was a multi-step project, which consisted of (1) identification of barriers to STI testing (May-June 2012) and baseline testing frequencies (March 2011 – September 2012); (2) program implementation (January – April 2013); and (3) program effectiveness (April 2013 – March 2014) and acceptability evaluation at Madison Clinic (December 2013 – January 2014). Step one 8 and parts of step two and three 17 have been previously described. Prior to implementation, we conducted five educational sessions to clinicians and nursing staff to allow all providers the opportunity to attend a session.…”
Section: Methodsmentioning
confidence: 99%
“…Despite that recommendation, there is evidence that MSM may not be offered quarterly screening as recommended [93]. A 2009 study in Ontario found that only 55% of HIV infected MSM received annual syphilis screening [94].…”
Section: Preventionmentioning
confidence: 99%